AB0734 The Shades of Anti-JO1 Positive Antisynthetase Syndrome in a Hungarian Cohort. (9th June 2015) - Griger, Z.; Szabό, K.; Nagy-Vincze, M.; Bodoki, L.; Hodosi, K.; Zilahi, E.; Dankό, K.
Abstract : Background: The most frequent myositis specific antibody (MSA) in the serum of patients with idiopathic inflammatory myopathies is anti-Jo-1. The presence of anti-Jo-1 define a distinct clinical phenotype, antisynthetase syndrome (ASS), which is characterized by poor prognosis and multiple organ involvement, such as myositis, interstitial lung disease (ILD), non-erosive arthritis, Raynaud's phenomen, mechanic's hand, skin rashes, and fever. Objectives: The aim of this study was to determine the clinical, serological, laboratory and genetic features of anti-Jo1 positive patients followed by our department. Methods: Retrospective analysis of medical records of 49 patients (42 female, 7 male) were reviewed. Anti-Jo-1 titer was detected with enzyme-linked immunosorbent assay. HLA DRB1, DQA1 and DQB1 genotype was determined using commercial sequence-specific oligonucleotide kit. Statistical analysis was performed using Pearson Chi 2, Fisher exact test, or Spearman correlation. Results: The median age at diagnosis was 43±13, 28 years (range: 18-70), 48 patients exhibited myositis (98%), 35 ILD (73%), 43 arthritis (88%), 32 Raynaud's phenomen (65%), 21 fever (43%), 16 mechanic's hand (33%), 27 skin rash (55%) and 6 dysphagia (12%). We could detect significant correlation between the initial anti-Jo-1 titer and the first CK (R=0, 328; p=0, 003) and CRP (R=0, 374; p=0, 016) level. Furthermore anti-Jo1 levels during disease course had significant correlation to the corresponding CK (R=0, 497; p<0.001), and CRP (R=0, 325; p<0.001) level. The most frequent antibody besides anti-Jo-1 was anti-SSA (28/49; 57%). The anti-Jo-1+/SSA+ population had younger age at the diagnosis (36, 12±11, 08 vs. 47, 22±12, 87; p=0, 004), lower rate of ILD (53% vs. 81%; p=0, 039), but higher maintaining steroid (methylprednisolone) dose (9, 53 mg vs. 3, 7 mg; p=0, 031) compared to the Jo-1+/SSA- group. Higher (≥8 mg) maintaining steroid therapy was associated with higher initiating CRP (36, 34 vs. 17, 84 mg/l; p=0, 014) ESR (33, 87 vs. 19, 81 mm/h; p=0, 032) level and higher presence of fever (67% vs. 37%; p=0, 038) at diagnosis but not with initiating CK (p=0, 374), LDH (p=0, 224) level or ILD presence (p=1). 68, 96% of the patients were HLA DRB1*03 positive, where the CK level at diagnosis was significantly lower compared to the HLA DRB1*03 negative patients (2816, 30 vs. 5969, 44 U/l; p=0.04). 58.62% of the patients were positive for HLA DQA1*0501-DQB1*0201 haplotype, but no significant correlation was found regarding to any clinical or laboratory features. Conclusions: Our results confirm previously reported data from other centers considering the clinical features of anti-Jo1 positive patients. HLA DRB1*03 positivity was associated with lower CK level but has no influence on clinical or serological features. It seems that anti-Jo1 level might reflect disease activity; ESR, CRP levels, associated fever and anti-SSA positivity at the diagnosis could be considered as prognostic markers. Disclosure of Interest: None declared